Fake News in the Social Media of the Trans-Baikal Territory: The War Against the Axiology of Society - Myasnikova, Tsyrigma Ts; Safronova, Olga V.; Tolstokulakova, Yulia V. (Gumanitarnyj vektor, 2023)
The relevance of the research is caused by the necessity of studying the phenomenon of fakeness, which has become the main problem in the information-psychological warfare against our country. Mass distribution of deliberately false information inevitably transforms the spiritual and moral values of society. Thus, the purpose of the research is to study this phenomenon in social media in the context of the influence on the fundamental values of society based on the content analysis of specialized Internet resources that are dedicated to reveal fakes and distributed in the Transbaikal Territory.The authors of the research have studied the phenomenon of fakes in the practice of modern social media. Based on the content analysis of the telegram channel "War against fakes. Zabaikalye", communities "Lapsha media", "Chita", "Zabaikalye. Oh i Novosti", "Politjoystick", "Notes from the East", "Nochnoi K", "CHITAGRAM Chita / News / Road Accident", the specificity of fake information in the Trans-Baikal Territory is determined with a focus on the subject of false information disseminated at the federal level. In total, 1980 posting contents published by these media resources were studied for the period from February 27, 2022 to May 3, 2023. The authors of the article relied on a discursive analysis, which helped to reveal specific unreliable content of materials and relate them with the agenda. The authors also used the sociocultural approach which was focused on the values that contribute to national identity values and make it possible to reveal the degree of influence of fake news on the traditional values of modern Russian society. The descriptive-analytical method helped with the theoretical understanding and systematization of the information about unreliable content. Based on the research, the authors came to the conclusion that the dissemination of false information is aimed at discrediting the main institutions of statehood – state authority, the army, as well as the foundations of the social structure – unity, catholicity, spirituality. Under influence of fake cases, Russian society is going through depreciation of traditional values such as patriotism, catholicity, spirituality, love, non-covetousness.